Hydrothermal synthesis of coccolith rich chalk to hydroxyapatite. (1st January 2012) - Fee, Kathryn; Walker, Gavin M.; Dunne, Nicholas J.; Buchanan, Fraser J.
Calcium carbonates originating from marine sources show unique pore structure and nano-architecture, offering potential in the field of hard tissue engineering. It is hypothesised that the use of naturally-sourced raw materials for the synthesis of hydroxyapatite (HA), as a component of a hard tissue constructs, enables enhanced bone remodelling due to the biomimetic physical-chemical characteristics of the HA. The aim of this study was to convert coccolith rich chalk to HA with the potential application of aiding bone tissue regeneration. This was attained by using a hydrothermal technique at an ambient pressure and low temperature 100ºC in an alkaline environment. The chalk was characterised using ICP, TGA, XRD and SEM to determine the physiochemical properties both pre-and post-synthesis. The results confirmed a high rate of conversion to HA at 93.7%. In addition the synthesised HA preserved the unique structure of the coccoliths which could be beneficial in bone repair applications.